2017
DOI: 10.1002/2017ms001117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiple Scattering on Longwave Radiative Transfer Involving Clouds

Abstract: General circulation models (GCMs) are extensively used to estimate the influence of clouds on the global energy budget and other aspects of climate. Because radiative transfer computations involved in GCMs are costly, it is typical to consider only absorption but not scattering by clouds in longwave (LW) spectral bands. In this study, the flux and heating rate biases due to neglecting the scattering of LW radiation by clouds are quantified by using advanced cloud optical property models, and satellite data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 58 publications
11
39
1
Order By: Relevance
“…The results showed a weak impact on downward flux at the surface as well. The spectral results of the cloud LW scattering effect on flux in Figure 2 are consistent with the band-by-band LW flux biases by neglecting scattering in Kuo et al [18].…”
Section: Standalone Radiative Transfer Model Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The results showed a weak impact on downward flux at the surface as well. The spectral results of the cloud LW scattering effect on flux in Figure 2 are consistent with the band-by-band LW flux biases by neglecting scattering in Kuo et al [18].…”
Section: Standalone Radiative Transfer Model Resultssupporting
confidence: 86%
“…In our study, the cumulative LW scattering effect on OLR is 2-6 W m −2 , and it is comparable with 4-8 W m −2 in Chou et al [6], 4 W m −2 in Li [7] and Li and Fu [10], and 6-8 W m −2 in Joseph and Min [17]. Kuo et al [18] demonstrated that the LW scattering in the far-infrared and atmospheric window regions (10-1390 cm −2 ) mainly contribute to the biases in spectral fluxes, which is consistent with our results in Figure 2.…”
Section: Standalone Radiative Transfer Model Resultssupporting
confidence: 85%
See 3 more Smart Citations